Envolvimento do sistema dopaminérgico na sensibilização comportamental ao femproporex - Alcantara, Luciana Mara Alvino; Planeta, Cleopatra da Silva [UNESP]; Delucia, Roberto (My University, 2002)
The effects of repeated administration of fenproporex (FEN) on motor activity of rats were studied. FEN-treated group (5.0 mg/kg, i.p., single dose, 7 consecutive days), showed a marked increase in the motor activity of rats, indicating that the drug induced behavioral sensitization. Repeated coadministration of haloperidol prevented the development of sensitization to repeated administration of FEN. Repeated administration of FEN increased also locomotor activity measured in the open field, ratifying the occurence of sensitization. These findings indicated development of sensitization to repeated FEN administration and that the dopamine system might be involved in the mechanism of sensitization.
The envolvement of the dopamine system in the behavioral sensitazion to fenproporex (FEN)
Keywords: Behavioral sensitization; Dopamine system; Fenproporex; fenproporex; haloperidol; animal experiment; animal model; behavior modification; controlled study; dopamine release; dose time effect relation; drug inhibition; drug mechanism; drug sensitization; locomotion; motor activity; nonhuman; open field behavior; rat; single drug dose